Quasielastic and low-energy inelastic neutron scattering study of HoCrO3 by high resolution time-of-flight neutron spectroscopy. (3rd November 2017) - Chatterji, T; Demmel, F; Jalarvo, N; Podlesnyak, A; Kumar, C M N; Xiao, Y; Brückel, T
Abstract: In order to understand the origin of the huge quasielastic magnetic scattering observed previously with a back-scattering neutron spectrometer, we have re-investigated the low energy excitations in HoCrO3 by inelastic neutron scattering in a much wider energy range with time-of-flight neutron spectrometers. The inelastic signals are due to the excitations between the ground state doublet of the Ho ion. The quasielastic signal is due to the fluctuation of the disordered Ho moments. At low temperature the intensity of quasielastic scattering is small. It starts increasing as the temperature increases above 30 K. At the same temperature, the elastic intensity due to Ho moment ordering decreases in a similar way. This observation strengthens the hypothesis that the quasielastic scattering is due the fluctuations of the disordered Ho moments. The time scale of fluctuations has been determine from the quasielastic scattering and was found to vary from about 22 ps at T = 70 K to about 2.5 ps at T = 160 K. The stretched exponential line shape indicates a distribution of decay rates at low temperatures.